122 Neurological manifestations of haemophagocytic lymphohistiocytosis. Issue 6 (27th May 2022) - Brown, Rachel; Amarnani, Raj; Flower, Luke; Manson, Jessica; Carr, Aisling
Abstract : Secondary (acquired) haemophagocytic lymphohistiocytosis (HLH) is a hyperinflammatory syndrome which can occur in the context of infection, malignancy or rheumatological disease and is associated with high mortality. Early recognition facilitates access to effective biological therapies and engage- ment with specialist MDTs which focus on managing the underlying trigger. Neurological manifestations are associated with poor prognosis but are not well described. We retrospectively reviewed 40 cases of secondary HLH in UCLH/NHNN; 25 had neurological compli- cations. Median age at onset: 36 years (range 11–79); 8 females. Causes of HLH were haematological malignancy (14), rheumatological disease (3), infection (2) and other/unknown (6). Neurological involve- ment portended higher morbidity and mortality: 21/40 ICU support; 19/40 in hospital death (15/25 and 16/25 with neurology). Neurological presentations included confusion (10) and reduced consciousness (5), headache (7), neuropathy (3) and myopathy (1). Based on symptomatology, radiological, CSF and metabolic and histological information we propose mechanistic causality of neurological manifesta- tions into: disease infiltration (13/25), metabolic (12/25), iatrogenic (2/25). The role of the cytokine storm in metabolic neurological derangement requires further investigation. We designed a minimal neurology dataset to improve prospective data collection instituted via the UK HiHASC (Hyperinflammatory and HLH Across Speciality Collaboration). A management algorithm is in development. rachel: brown@ucl.ac.uk|ABN Bursary 86